Mechanical and microstructure characterization of cementitious full depth reclamation mixtures - Ammu B Crusho; Vishnu Radhakrishnan; K. Sridhar Reddy; Veeraragavan Amirthalingam; Harisankar Asadevi (Innovative Infrastructure Solutions, 2026)

Shrimp immune responses and antimicrobial peptides: an overview with emphasis on Vibrio infection - Naveenkumar Radhakrishnan; Akshaya Panigrahi; B. Naveen Rajeshwar; Megha Kadam Bedekar (Aquaculture International, 2026)

Comparison of clinical, radiological and outcome parameters in patients with progressive multifocal leukoencephalopathy (PML) with and without HIV infection: a cohort study - Farsana Mustafa; Anuj Ajayababu; Ajay Garg; Megha Brijwal; Divyani Garg; Manish Soneja; Aashish Choudhary; Lalit Dar; Shariq A. Shah; Venugopalan Y Vishnu; Animesh Ray; Neeraj Nischal; et al. (Journal of NeuroVirology, 2025)

Novel o-Terphenyl Luminophores for Optoelectronic Devices: Synthesis, Photophysical, Electrochemical, and Thermal Analysis - Amarsinh R. Mainak; Pranjali S. Kewate; Vasanti B. Shabade; Vishnu V. Kutwade; Radhakrishnan M. Tigote; Netaji K. Desai; Sidram R. Pujari (Journal of Fluorescence, 2025)

Bacillus licheniformis and commercial fungicides exhibit high potential against major pathogens inciting grain discolouration disease in rice, Oryza sativa L. - P. K. Amrith; M. Surendran; N. V. Radhakrishnan; Susha S. Thara; T. Anuradha; B. Ajay (Indian Phytopathology, 2025)

Comparative study on the performance of cement treated base layer materials and fly ash-based geopolymer base layer materials - B. Sravanthi; Vishnu Radhakrishnan; Jithin Kurian Andrews; Asim Sarfaraj Rahimoddin Saudagar (Innovative Infrastructure Solutions, 2025)

Quantifying abnormal writing kinematics in writer’s cramp using a novel software platform - Kavadisseril Vivekanandan Vysakha; Vineeth Radhakrishnan; Praveen James; B. Suresh Kumar; Ashish Anand Susvirkar; Gangadhara Sarma; Ajith Cherian; K. P. Divya; Syam Krishnan Nair; Asha Kishore (Acta Neurologica Belgica, 2024)

Uncovering Sex-Specific Epigenetic Regulatory Mechanism Involving H3k9me2 in Neural Inflammation, Damage, and Recovery in the Internal Carotid Artery Occlusion Mouse Model - Mydhili Radhakrishnan; Vincy Vijay; B. Supraja Acharya; Papia Basuthakur; Shashikant Patel; Kalyani Soren; Arvind Kumar; Sumana Chakravarty (NeuroMolecular Medicine, 2024)

Pixel Reduction of High-Resolution Image Using Principal Component Analysis - Ramachandran Radhakrishnan; Manimegalai Thirunavukkarasu; R. Thandaiah Prabu; G. Ramkumar; S. Saravanakumar; Anitha Gopalan; V. Rama Lahari; B. Anusha; Shaik Hasane Ahammad; Ahmed Nabih Zaki Rashed; Md. Amzad Hossain (Journal of the Indian Society of Remote Sensing, 2024)

Synthesis and characterization of gold nanoparticles using Brevibacterium casei (SOSIST-06) isolated from Southern Ocean water samples and their in vitro and in silico anti-WSSV activity - R. Namitha; B. Abirami; B.S. Anoop; D.V. Diya Dominic; Ahna Ameer; K. Manigundan; M. Radhakrishnan; P. Santhiya; Parli V. Bhaskar; K. Govindaraju; I.S. Bright Singh; G. Dharani (Aquaculture, 2024)

Antiviral activity of Turbinaria ornata against white spot syndrome virus in freshwater crab (Paratelphusa hydrodromous) - Bharath Raja; Naveen Arakkal Thaiparambil; Kariyanna B; Vidya Radhakrishnan; Sudhakaran Raja (Aquaculture International, 2023)

Hanging in the air: tree moss diatoms from Indo-Burma biodiversity hot spot of India - C. Radhakrishnan; M. Yogeshwaran; B. Karthick (Aerobiologia, 2022)

Relative abundance of PGRs in the liquid endosperm of young nuts of Cocos nucifera L. parental cultivars and their reciprocal hybrids - V. V. Amritha; K. G. Ajith Kumar; Parvathy S. Nair; N. V. Radhakrishnan; K. Prathapan; B. N. Bessy Raj (Plant Physiology Reports, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Anti-inflammatory effect and mechanism of action of ellagic acid-3,3′,4-trimethoxy-4′- O -α-L-rhamnopyranoside isolated from Hopea parviflora in lipopolysaccharide-stimulated RAW 264.7 macrophages - B. Prabha; S. Sini; T. S. Priyadarshini; P. Sasikumar; Greeshma Gopalan; Jayesh P. Joseph; M. M. Jithin; V. V. Sivan; P. Jayamurthy; K. V. Radhakrishnan (Natural Product Research, 2021)

Promalabaricone B from Myristica fatua Houtt. seeds demonstrate antidiabetic potential by modulating glucose uptake via the upregulation of AMPK in L6 myotubes - B. Prabha; S. Sini; D. R. Sherin; S. Neethu; K. B. Rameshkumar; T. K. Manojkumar; P. Jayamurthy; K. V. Radhakrishnan (Natural Product Research, 2021)

Fatty acid desaturase-2 (ahFAD2) mutant alleles in peanut (Arachis hypogaea L.) pre-breeding lines: an insight into the source, features, discourse, and selection of novel pre-breeding lines - J. H. Kamdar; M. D. Jasani; B. C. Ajay; Kirti Rani; N. Manivannan; R. P. Vasanthi; K. L. Dobariya; M. K. Pandey; P. Janila; T. Radhakrishnan; R. K. Varshney; S. K. Bera (Genetic Resources and Crop Evolution, 2021)

Water deficit-induced oxidative stress and differential response in antioxidant enzymes of tolerant and susceptible tea cultivars under field condition - M. Nalina; S. Saroja; M. Chakravarthi; R. Rajkumar; B. Radhakrishnan; K. N. Chandrashekara (Acta Physiologiae Plantarum, 2021)

Combined Effect of Pseudomonas spp. Consortium and Fertilizer with Micronutrients on Enhanced yield of Amaranthus tricolor (L.) - S. Soumya; S. Sreejith; K. Shibil Shad; P. Anusha; B. Swathy; R. Renikrishna; S. Saranya; P. Jishma; E. K. Radhakrishnan; A. Remakanthan (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2020)

G × E interactions in QTL introgression lines of Spanish-type groundnut (Arachis hypogaea L.) - A. L. Rathnakumar; Surendra S. Manohar; Hajisaheb L. Nadaf; Sudam C. Patil; Milind P. Deshmukh; P. P. Thirumalaisamy; Narendra Kumar; H. B. Lalwani; P. Nagaraju; Basavaraj Yenagi; S. S. Patil; J. Suryawanshi; et al. (Euphytica, 2020)

Distribution of multi-virulence factors among Aeromonas spp. isolated from diseased Xiphophorus hellerii - Soumya Das; R. Aswani; B. Jasim; K. S. Sebastian; E. K. Radhakrishnan; Jyothis Mathew (Aquaculture International, 2020)

Epigenetic Modifier Based Enhancement of Piperine Production in Endophytic Diaporthe sp. PF20 - B. Jasim; Neethu Sahadevan; S. Chithra; Jyothis Mathew; E. K. Radhakrishnan (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Plant Growth Promoting Endophytic Serratia sp. ZoB14 Protecting Ginger from Fungal Pathogens - Rohini Sabu; R. Aswani; P. Jishma; B. Jasim; Jyothis Mathew; E. K. Radhakrishnan (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Chemical and biological studies on Bridelia ferruginea grown in Nigeria - Michael Afolayan; Radhakrishnan Srivedavyasasri; Olayinka T. Asekun; Oluwole B. Familoni; Samir A. Ross (Natural Product Research, 2019)

Phytochemical study of Piliostigma thonningii, a medicinal plant grown in Nigeria - Michael Afolayan; Radhakrishnan Srivedavyasasri; Olayinka T. Asekun; Oluwole B. Familoni; Abayomi Orishadipe; Fazila Zulfiqar; Mohamed A. Ibrahim; Samir A Ross (Medicinal Chemistry Research, 2018)

Improving oil quality by altering levels of fatty acids through marker-assisted selection of ahfad2 alleles in peanut (Arachis hypogaea L.) - Sandip K. Bera; Jignesh H. Kamdar; Swati V. Kasundra; Pitabas Dash; Anil K. Maurya; Mital D. Jasani; Ajay B. Chandrashekar; N. Manivannan; R. P. Vasanthi; K. L. Dobariya; Manish K. Pandey; Pasupuleti Janila; et al. (Euphytica, 2018)

Differential Modulation of Endophytic Microbiome of Ginger in the Presence of Beneficial Organisms, Pathogens and Both as Identified by DGGE Analysis - Rohini Sabu; R. Aswani; Priya Prabhakaran; B. Krishnakumar; E. K. Radhakrishnan (Current Microbiology, 2018)

New tetranorlabdanoic acid from aerial parts of Salvia aethiopis - Radhakrishnan Srivedavyasasri; Miriah B. White; Tatyana S. Kustova; Nadezhda G. Gemejiyeva; Charles L. Cantrell; Samir A. Ross (Natural Product Research, 2018)

Spectral and Lensing Characteristics of Gel-Derived Strontium Tartrate Single Crystals Using Dual-Beam Thermal Lens Technique - I. Rejeena; V. Thomas; S. Mathew; B. Lillibai; V. P. N. Nampoori; P. Radhakrishnan (Journal of Fluorescence, 2016)

Spectral and Non Radiative Decay Studies of Lead Di Bromide Single Crystals by Mode Matched Thermal Lens Technique - I. Rejeena; B. Lillibai; V. Thomas; V. P. N. Nampoori; P. Radhakrishnan (Journal of Fluorescence, 2016)

Transgenic peanut overexpressing mtlD gene confers enhanced salinity stress tolerance via mannitol accumulation and differential antioxidative responses - Kirankumar G. Patel; Viralkumar B. Mandaliya; Gyan P. Mishra; Jentilal R. Dobaria; Radhakrishnan Thankappan (Acta Physiologiae Plantarum, 2016)

Layer-specific interhemispheric functional connectivity in the somatosensory cortex of rats: resting state electrophysiology and fMRI studies - Kwangyeol Baek; Woo Hyun Shim; Jaeseung Jeong; Harsha Radhakrishnan; Bruce R. Rosen; David Boas; Maria Franceschini; Bharat B. Biswal; Young R. Kim (Brain Structure and Function, 2016)

Phytostimulatory and hardening period-reducing effects of plant-associated bacteria on micropropagated Musa acuminata cv. Grand Naine - E. P. Suada; B. Jasim; C. J. Jimtha; G. P. Gayatri; E. K. Radhakrishnan; A. Remakanthan (In Vitro Cellular & Developmental Biology - Plant, 2015)

Genotype–phenotype analysis of von Hippel–Lindau syndrome in fifteen Indian families - Narendranath Vikkath; Sindhu Valiyaveedan; Sheela Nampoothiri; Natasha Radhakrishnan; Gopal S. Pillai; Vasantha Nair; Ginil Kumar Pooleri; Georgie Mathew; Krishnakumar N. Menon; Prasanth S. Ariyannur; Ashok B. Pillai (Familial Cancer, 2015)

PrfA regulation offsets the cost of L isteria virulence outside the host - Radhakrishnan B. Vasanthakrishnan; Aitor de las Heras; Mariela Scortti; Caroline Deshayes; Nick Colegrave; José A. Vázquez‐Boland (Environmental Microbiology, 2015)
Summary Virulence traits are essential for pathogen fitness, but whether they affect microbial performance in the environment, where they are not needed, remains experimentally unconfirmed. We investigated this question with the facultative pathogen L isteria monocytogenes and its PrfA virulence regulon. PrfA ‐regulated genes are activated intracellularly ( PrfA ‘ ON ’) but shut down outside the host ( PrfA ‘ OFF ’). Using a mutant PrfA regulator locked ON ( PrfA *) and thus causing PrfA ‐controlled genes to be constitutively activated, we show that virulence gene expression significantly impairs the listerial growth rate (μ) and maximum growth (A) in rich medium. Deletion analysis of the PrfA regulon and complementation of a L. monocytogenes mutant lacking all PrfA ‐regulated genes with PrfA* indicated that the growth reduction was specifically due to the unneeded virulence determinants and not to pleiotropic regulatory effects of PrfA ON . No PrfA *‐associated fitness disadvantage was observed in infected eukaryotic cells, where PrfA ‐regulated virulence gene expression is critical for survival. Microcosm experiments demonstrated that the constitutively virulent state strongly impaired L . monocytogenes performance in soil, the natural habitat of these bacteria. Our findings provide empirical proof that virulence carries a significant cost to the pathogen. They also experimentally substantiate the assumed, although not proven, key role of virulence gene regulation systems in suppressing the cost of bacterial virulence outside the host.

Effect of endophytic Bacillus sp. from selected medicinal plants on growth promotion and diosgenin production in Trigonella foenum-graecum - B. Jasim; P. R. Geethu; Jyothis Mathew; E. K. Radhakrishnan (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Phenazine carboxylic acid production and rhizome protective effect of endophytic Pseudomonas aeruginosa isolated from Zingiber officinale - B. Jasim; C. Anisha; Sabu Rohini; Jacob Manoj Kurian; Mathew Jyothis; E. K. Radhakrishnan (World Journal of Microbiology and Biotechnology, 2014)

ttime: an R Package for Translating the Timing of Brain Development Across Mammalian Species - Radhakrishnan Nagarajan; Richard B. Darlington; Barbara L. Finlay; Barbara Clancy (Neuroinformatics, 2010)

Rooting and shooting: dual function of thidiazuron in in vitro regeneration of soybean (Glycine max. L) - R. Radhakrishnan; A. Ramachandran; B. D. Ranjitha Kumari (Acta Physiologiae Plantarum, 2009)

Analysis of diallel cross for some physical-quality traits in peanut (Arachis hypogaea L.) - K. Hariprasanna; Chuni Lal; T. Radhakrishnan; H. K. Gor; B. M. Chikani (Euphytica, 2008)

Enteromorpha compressa (L.) Greville an edible green alga as a source of antiallergic principle (S) - B. Venkata Raman; D. N. Rao; T. M. Radhakrishnan (Indian Journal of Clinical Biochemistry, 2004)

Genetic association analysis of KCNQ3 and juvenile myoclonic epilepsy in a South Indian population - J. Vijai; A. Kapoor; H. M. Ravishankar; P. J. Cherian; A. S. Girija; B. Rajendran; G. Rangan; S. Jayalakshmi; S. Mohandas; K. Radhakrishnan; A. Anand (Human Genetics, 2003)

Control of the coconut pest Oryctes rhinoceros L. using the Oryctes virus - Murali Gopal; Alka Gupta; B. Sathiamma; C. P. Radhakrishnan Nair (International Journal of Tropical Insect Science, 2001)